2021
DOI: 10.3389/fpsyg.2021.721716
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence of Slowed Time Experience During the COVID-19 Pandemic: Two Longitudinal Studies in France

Abstract: The home confinement imposed on people to fight the COVID-19 pandemic interrupted the flow of time by disrupting daily life, making them feel that time was passing slowly. The aim of this longitudinal study was to evaluate the evolution over time of this subjective experience of time and its significant predictors (boredom, decreased happiness, life rhythm, and sleep quality). Twso samples of French participants were followed up: the first for several weeks during the first lockdown (April 2020) and then 1year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 37 publications
12
46
0
Order By: Relevance
“…High boredom, anger and sadness, as well as low levels of contentment, satisfaction and relaxation were associated with a longer DJ. These results, in particular the association of asubjective deceleration as well as longer duration with negative affect are in line with findings from studies conducted in Italy [ 2 ], France [ 5 7 ], the UK [ 3 , 4 ], Brazil [ 8 ], Uruguay [ 9 ], and Germany [ 10 ]. This finding is, therefore, very robust and largely independent of the cultural backgrounds.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…High boredom, anger and sadness, as well as low levels of contentment, satisfaction and relaxation were associated with a longer DJ. These results, in particular the association of asubjective deceleration as well as longer duration with negative affect are in line with findings from studies conducted in Italy [ 2 ], France [ 5 7 ], the UK [ 3 , 4 ], Brazil [ 8 ], Uruguay [ 9 ], and Germany [ 10 ]. This finding is, therefore, very robust and largely independent of the cultural backgrounds.…”
Section: Discussionsupporting
confidence: 89%
“…Our main result is that changes in the perceived passage of time during the pandemic, as concluded by many authors in several studies from different countries (e.g., [ 2 , 3 , 4 , 7 , 9 ]), can be confirmed even when comparing the passage of the previous year to a baseline: the previous year was generally judged as having passed markedly slower by participants who provided their judgments during the pandemic (note that the pandemic covered this whole year) compared to participants who made these judgments before the pandemic. This corresponds with results from a UK study, where almost 40% of the participants reported the time since the beginning of the pandemic (8 months) as longer than a normal 8-month period [ 4 ].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…To capture the temporal phenomenology of the felt passage of time, individuals can rate their feeling of how fast time is passing over a certain lapse of time using a VAS. This approach was used in previous studies (Droit -Volet et al, , 2021Martinelli et al, 2020;Ogden, 2020Ogden, , 2021. In Blursday, we asked participants to rate their feeling of the passage of time over the last few days.…”
Section: Passage Of Time On the Scale Of A Few Daysmentioning
confidence: 99%
“…In French surveys, participants answered the question: "What are your feelings about the speed of passage time?" (Droit- Volet et al, , 2021Martinelli et al, 2020). The question was asked in reference to the individuals' autobiographical recall of their experienced passage of time before the lockdown, then asked three times during lockdown in reference to the "now", to "yesterday", and to "one week ago".…”
Section: Introductionmentioning
confidence: 99%